2017
DOI: 10.1080/19012276.2017.1381037
|View full text |Cite
|
Sign up to set email alerts
|

Can a managerial intervention focusing on job demands, job resources, and personal resources improve the work situation of employees?

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
1
0
3
Order By: Relevance
“…Despite these encouraging findings, other studies have failed to find any positive effects of leadership training on working conditions (Hansen, Landstad, Gunderse, & Vinberg, 2016) and well-being (Elo, Ervasti, Kuosma, & Mattila-Holappa, 2014;Hansen et al, 2016). Nylén, Lindfors, Le Blanc, Aronsson, and Sverke (2018) found that unreasonable tasks increased in the control group, but not in the group of employees whose leaders received the intervention. No improvements were detected in other job demands, nor in personal or job resources.…”
Section: Leading Well:mentioning
confidence: 89%
“…Despite these encouraging findings, other studies have failed to find any positive effects of leadership training on working conditions (Hansen, Landstad, Gunderse, & Vinberg, 2016) and well-being (Elo, Ervasti, Kuosma, & Mattila-Holappa, 2014;Hansen et al, 2016). Nylén, Lindfors, Le Blanc, Aronsson, and Sverke (2018) found that unreasonable tasks increased in the control group, but not in the group of employees whose leaders received the intervention. No improvements were detected in other job demands, nor in personal or job resources.…”
Section: Leading Well:mentioning
confidence: 89%
“…La primera búsqueda consideró las palabras en inglés y en español: factores psicosociales, intervención y organización; se localizaron un total de 16 374 registros, 13 de los cuales fueron duplicados, se excluyeron 16 327 registros por no ser de los primeros 50 por orden de relevancia en la base de datos Google Académico; dos artículos no cumplieron con los criterios de inclusión, quedando un total de 32 que se analizaron tal como se muestra en la figura 1. Se encontró que las publicaciones de estudios de factores psicosociales de riesgo con intervención fueron 10 y de ellas cinco reportan resultados de la intervención (Biggs et al, 2014;Hammer et al, 2015;Mathisen et al, 2017;Nylén et al, 2018;Potter et al, 2017;), mismos que fueron analizados para conocer entre otros aspectos la metodología de intervención y si se contempló una gestión integral. En la tabla 1 se muestra el título del artículo, el año de publicación y la base de datos donde se localizó; los autores y país de origen; la teoría, modelo o metodología utilizada; y el diseño del estudio que indica si se hizo intervención.…”
Section: Resultsunclassified
“…En el segundo caso, los recursos del trabajo (retroalimentación, control, claridad de metas) y los recursos personales (señalización y estrategias de establecimiento de límites) no presentaron cambios significativos, por el contrario, las demandas del trabajo (carga de trabajo, tareas innecesarias y tareas irrazonables) se incrementaron significativamente con el tiempo (Nylén et al, 2018). Para el tercer caso, no se demostraron efectos significativos en demandas del trabajo, liderazgo tensión psicológica intenciones de rotación.…”
Section: Discussionunclassified
See 1 more Smart Citation